Terminology for describing normally sited and ectopic pregnancies on ultrasound: ESHRE recommendations for good practice. Issue 4 (16th December 2020) - ,; Kirk, Emma; Ankum, Pim; Jakab, Attila; Le Clef, Nathalie; Ludwin, Artur; Small, Rachel; Tellum, Tina; Töyli, Mira; Van den Bosch, Thierry; Jurkovic, Davor
Abstract: STUDY QUESTION: What recommendations can be provided to improve terminology for normal and ectopic pregnancy description on ultrasound? SUMMARY ANSWER: The present ESHRE document provides 17 consensus recommendations on how to describe normally sited and different types of ectopic pregnancies on ultrasound. WHAT IS KNOWN ALREADY: Current diagnostic criteria stipulate that each type of ectopic pregnancy can be defined by clear anatomical landmarks which facilitates reaching a correct diagnosis. However, a clear definition of normally sited pregnancies and a comprehensive classification of ectopic pregnancies are still lacking. STUDY DESIGN, SIZE, DURATION: A working group of members of the ESHRE Special Interest Group in Implantation and Early Pregnancy (SIG-IEP) and selected experts in ultrasound was formed in order to write recommendations on the classification of ectopic pregnancies. PARTICIPANTS/MATERIALS, SETTING, METHODS: The working group included nine members of different nationalities with internationally recognised experience in ultrasound and diagnosis of ectopic pregnancies on ultrasound. This document is developed according to the manual for development of ESHRE recommendations for good practice. The recommendations were discussed until consensus by the working group, supported by a survey among the members of the ESHRE SIG-IEP. MAIN RESULTS AND THE ROLE OF CHANCE: A clear definition of normally sited pregnancy on ultrasound scan is important to avoid misdiagnosis of uterine ectopic pregnancies. A comprehensive classification of ectopic pregnancy must include definitions and descriptions of each type of ectopic pregnancy. Only a classification which provides descriptions and diagnostic criteria for all possible locations of ectopic pregnancy would be fit for use in routine clinical practice. The working group formulated 17 recommendations on the diagnosis of the different types of ectopic pregnancies on ultrasound. In addition, for each of the types of ectopic pregnancy, a schematic representation and examples on 2D and 3D ultrasound are provided. LIMITATIONS, REASONS FOR CAUTION: Owing to the limited evidence available, recommendations are mostly based on clinical and technical expertise. WIDER IMPLICATIONS OF THE FINDINGS: This document is expected to have a significant impact on clinical practice in ultrasound for early pregnancy. The development of this terminology will help to reduce the risk of misdiagnosis and inappropriate treatment. STUDY FUNDING/COMPETING INTEREST(S): The meetings of the working group were funded by ESHRE. T.T. declares speakers' fees from GE Healthcare. The other authors declare that they have no conflict of interest. TRIAL REGISTRATION NUMBER: N/A DISCLAIMER: This Good Practice Recommendations (GPR) document represents the views of ESHRE, which are the result of consensus between the relevant ESHRE stakeholders and where relevant based on the scientific evidence available at the time of preparation. ESHRE's GPRs should be used for informational and educational purposes. They should not be interpreted as setting a standard of care or be deemed inclusive of all proper methods of care nor exclusive of other methods of care reasonably directed to obtaining the same results. They do not replace the need for application of clinical judgement to each individual presentation, nor variations based on locality and facility type. Furthermore, ESHRE's GPRs do not constitute or imply the endorsement, recommendation or favouring of any of the included technologies by ESHRE.